Determination of linear density of cotton ribbons by photoelectric method - Elmurod Jamoldinovich Alikhonov (Open Science LLC, 2021)
The current problem of automatic control and stabilization of the weight of cotton belts at the spinning mill is highlighted. Structural diagrams are given and the principle of operation of an optoelectronic device for automatic control and stabilization of the weight of cotton bands is described. The principle of the optoelectronic method for monitoring the linear density of cotton tapes is stated.